IgG4-Related Sclerosing Cholangitis Involving the Intrahepatic Bile Ducts Diagnosed with Liver Biopsy - Malene Theilmann Thinesen; Ove B. Schaffalitzky de Muckadell; Sönke Detlefsen (Case Reports in Pathology)
IgG4-related disease is characterized by lymphoplasmacytic inflammation and fibrosis, often leading to mass-forming lesions in different organs. When IgG4-related disease affects the bile ducts, it is called IgG4-related sclerosing cholangitis. A 74-year-old male complained of dysphagia and abdominal pain. Endoscopic retrograde cholangiography and magnetic resonance cholangiography revealed bile duct changes suspicious of a bile duct carcinoma or cholangitis. Liver biopsy showed storiform fibrosis, lymphoplasmacytic infiltration, obliterative phlebitis, and a portal-based inflammatory nodule with expansion of a portal tract. Hot spots revealed 339 IgG4-positive cells per high power field (HPF) and an IgG4/IgG ratio of 72%. Eight months earlier, an inguinal lymph node had been removed, showing expanded interfollicular zones and increased plasma cells. Hot spots revealed 593 IgG4-positive cells and an IgG4/IgG ratio of 92%. The serum IgG4 of the patient was elevated nearly 10 times upper limit of normal. The diagnosis of IgG4-related sclerosing cholangitis associated with IgG4-related lymphadenopathy was made. There was good response to treatment with prednisolone and azathioprine. The differentiation of IgG4-related sclerosing cholangitis from primary sclerosing cholangitis and bile duct carcinoma is often difficult. Liver biopsy only rarely contributes to this setting, but we describe and report in detail a case where liver biopsy showed a portal-based inflammatory nodule with the characteristic features of this disease.